2021
DOI: 10.4251/wjgo.v13.i9.1017
|View full text |Cite
|
Sign up to set email alerts
|

Association between intestinal neoplasms and celiac disease: A review

Abstract: Celiac disease (CD) is a chronic immune-mediated intestinal disease with genetic susceptibility. It is characterized by inflammatory damage to the small intestine after ingestion of cereals and products containing gluten protein. In recent years, the global prevalence rate of CD has been approximately 1%, and is gradually increasing. CD patients adhere to a gluten-free diet (GFD) throughout their entire life. However, it is difficult to adhere strictly to a GFD. Untreated CD may be accompanied by gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…In addition to CD, we believe that other underlying mechanisms contribute to the developing malignant neoplasms[ 3 ]. We believe that these facts would be a helpful to understand CD and EATL and these findings are highly pertinent and provide a context that helps understand those reported by Wang et al [ 1 ].…”
Section: To the Editormentioning
confidence: 52%
See 1 more Smart Citation
“…In addition to CD, we believe that other underlying mechanisms contribute to the developing malignant neoplasms[ 3 ]. We believe that these facts would be a helpful to understand CD and EATL and these findings are highly pertinent and provide a context that helps understand those reported by Wang et al [ 1 ].…”
Section: To the Editormentioning
confidence: 52%
“…I read with great interest the paper by Wang et al [ 1 ] in the issue 13 of World Journal of Gastrointestinal Oncology, a review article regarding the association between intestinal neoplasms and celiac disease. The authors showed that the total risk of small bowel cancer (SBC) and enteropathy-associated T cell lymphoma (EATL) increased in celiac disease (CD) patients.…”
Section: To the Editormentioning
confidence: 99%
“…This is particularly critical in populations with a high incidence of CD and the associated high mortality rate as a result of malignant transformation to EATL. Additionally, there is a need to further evaluate the strength of the protective effects of gluten-free diets on EATL via prospective cohorts and experimental studies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a study by Volta et al, an increase in CRC was only seen in individuals above the age of 60 [6]. Other studies showed no increase in the prevalence of colonic neoplasia in patients with CD [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%